FINANCIAL FEASIBILITY OF ROLLER BLIND FROM VETIVER WOVEN FABRIC - Ahmad Thoriq; Lukito Hasta Pratopo; Desviana Devanni Fajriyanti; Muhamad Arip (Arena Tekstil, 2022)
The vetiver woven roller blind is an environmentally friendly window covering innovation that can provide an aromatherapy scent produced by vetiver woven fabric. This study aims to analyze the financial feasibility of a roller blind production of vetiver woven fabric. The initial steps carried out in this study were the preparation of vetiver raw materials, the manufacture of vetiver woven fabrics, the manufacture of vetiver woven roller blinds, and financial analysis of the vetiver woven roller blinds that had been made. The results showed that the capacity of making vetiver woven fabric using a non-machine loom was 101.3 cm²/minute or equivalent to 72 m x 70 cm per month and 60-units of vetiver woven fabric roller blinds with a size of 120 cm x 70 cm were obtained. per month. The cost to produce 60-units of vetiver woven roller blinds is Rp16,988,300.00 per month and the HPP is Rp283,138.00 per unit. At the price of roller blinds for vetiver woven fabric Rp3,600.00 per cm2 or Rp302,400.00 per unit, the NPV value is Rp38,000,874.00, BCR is 1.05, IRR is 9.16%, and PBP in month 11th.